2013
DOI: 10.1111/jph.12125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc on the Development of Brown Spot in Rice

Abstract: Brown spot, caused by the fungus Bipolaris oryzae, is one of the most destructive diseases of rice. This study investigated the effect of zinc rates on the development of brown spot in rice. Rice plants (cv. ‘Metica‐1′) were grown in hydroponic culture amended with Zn rates (applied as ZnSO4.7H2O) of 0, 0.5, 1, 2 and 4 μm and inoculated with B. oryzae. The foliar concentration of Zn was determined. Leaf samples were assessed for disease severity, and then, area under brown spot progress curve (AUBSPC) was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Similar results were reported by Elamawi et al, (2016) on rice brown spot disease. In contrast to this investigation, Moreira et al, (2013) found that increasing Zn in leaf tissues was Egypt. J.…”
Section: Discussioncontrasting
confidence: 86%
“…Similar results were reported by Elamawi et al, (2016) on rice brown spot disease. In contrast to this investigation, Moreira et al, (2013) found that increasing Zn in leaf tissues was Egypt. J.…”
Section: Discussioncontrasting
confidence: 86%
“…Contrary results were observed by Lin and Xing 2008 which, phytotoxicity of commercially available ZnO nanoparticle to rye grass was reported. Moreira et al 2013 showed that high foliar concentration of Zn was associated with high concentrations of Zn in leaf tissues consequently increasing rice susceptibility to brown spot (Moreira et al 2013). According to Duffy (2007), the intensity of several diseases can be reduced or increased by supplying Zn to plants.…”
Section: Resultsmentioning
confidence: 99%
“…Supply of Zn can lead to increase or decrease in disease severity in plants (Duffy, 2007). Moreira et al (2013) observed a positive correlation between the elevated Zn concentration in leaves and its susceptibility to brown spot in rice. Though these effects of elevated levels of Zn were found selective.…”
Section: Environment Conservation Journalmentioning
confidence: 86%